Decreased Expression of Retinoblastoma Protein-Interacting Zinc-Finger Gene 1 Is Correlated With Poor Survival and Aggressiveness of Cervical Cancer Patients - Yang, Shanshan; Liu, Tianbo; Cheng, Haiyan; Wang, Zhao; Feng, Yue; Yan, Jiazhuo; Liu, Sijia; Zhang, Yunyan (Frontiers in Oncology, 2019)
Background Retinoblastoma protein-interacting zinc finger gene 1 (RIZ1) is a tumor suppressor deregulated in several human cancers. We aim to 1) explore RIZ1 expression in FIGO stages I-II cervical cancer tissues and its association with the clinical outcome of cervical cancer patients, 2) the role of RIZ1 in proliferation, apoptosis, migration, and invasion in cervical cancer cells. Methods The expression of RIZ1 in 268 cervical cancer tissues and 30 paired adjacent non-tumor tissues were assessed by immunohistochemistry. We also examined RIZ1 at mRNA and protein level in 20 paired fresh frozen cervical cancer tissues and the adjacent non-tumor tissue using real-time PCR and western blot. We then examined proliferation, apoptosis, migration, and invasion in two human cervical cancer cells, HeLa and SiHa, with overexpression of RIZ1. Results RIZ1 expression generally decreased in cervical cancer tissues. Decreased RIZ1 expression was significantly correlated with advanced FIGO stage (P=0.005), deep stromal invasion (P=0.001), lymphovascular space involvement (P=0.041), pelvic lymph node metastasis (P=0.005), and postoperative recurrence (P=0.002). Kaplan-Meier analysis demonstrated that patients with low RIZ1 expression had shorter overall survival (OS) and disease-free survival (DFS) than those with high RIZ1 expression. Multivariate analysis showed that RIZ1 was an independent prognostic factor for DFS (HR=2.184, 95%CI1.365-3.496, P=0.001) and OS (HR=1.899, 95%CI1.112-3.241, P=0.019). In vitro analysis demonstrated that overexpression of RIZ1 inhibited cell proliferation, migration, and invasion, but promoted apoptosis in HeLa and SiHa cells. Conclusion Down-regulation of RIZ1 may contribute to tumor migration, invasiveness, and poor survival of cervical cancer patients. RIZ1 may be a prognostic biomarker for cervical cancer patients.